2006
DOI: 10.1182/blood-2005-06-2508
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoma incidence patterns by WHO subtype in the United States, 1992-2001

Abstract: Age-specific and age-adjusted rates were compared by sex and race (white, black, Asian). Age-adjusted trends in incidence were estimated by sex and race using weighted least squares log-linear regression. Diverse incidence patterns and trends were observed by lymphoid neoplasm subtype and population. In the elderly (75 years or older), rates of diffuse large B-cell lymphoma (DLBCL) and follicular lymphoma increased 1.4% and 1.8% per year, respectively, whereas rates of chronic lymphocytic leukemia/small lympho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

74
1,150
13
46

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,502 publications
(1,283 citation statements)
references
References 78 publications
74
1,150
13
46
Order By: Relevance
“…Our findings are in agreement with previous results, showing the relatively higher proportions of patients with overall NHL and T/NK-cell neoplasms, and the relatively lower proportions of patients with FL, CLL/SLL, and HL among Korean individuals compared with those of Western populations (Supplementary Table III) [4][5][6][7][8][9][10][11][12][13][14][15][16][17]19,21,23,37].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our findings are in agreement with previous results, showing the relatively higher proportions of patients with overall NHL and T/NK-cell neoplasms, and the relatively lower proportions of patients with FL, CLL/SLL, and HL among Korean individuals compared with those of Western populations (Supplementary Table III) [4][5][6][7][8][9][10][11][12][13][14][15][16][17]19,21,23,37].…”
Section: Discussionsupporting
confidence: 92%
“…Although these data effectively characterize the subtype spectrum of lymphomas [18][19][20][21][22][23][24][26][27][28][29][30][31][32][33][34][35], most studies have excluded the majority of plasma cell neoplasms and leukemias (circulating phase). Therefore, these results may not be comparable with population-based incidence data for the entire spectrum of WHO classifications [10,42,43].…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…1 The clinical course of diff use large B-cell lymphoma has greatly changed over the past 10 years, since the introduction of the chimeric monoclonal anti-CD20 antibody rituximab for the treat ment of patients with lymphoma. A pivotal trial done in 1998 by the Groupe d'Etude des Lymphomes de l'Adulte (GELA) showed that combining rituximab with standard cyclophospha mide, doxorubicin, vincristine, and predni sone (CHOP) chemo therapy signifi cantly improved response, event-free survival, and overall survival compared with CHOP alone in patients older than 60 years.…”
Section: Introductionmentioning
confidence: 99%
“…Reactive lesions can mimic malignancy, a distinction which may be difficult. Fortunately, primary lymphomas of the SG are rare tumors, representing 1.7-3 % of all SG neoplasms [2,3], although the incidence may be on the rise [3][4][5].…”
Section: Introductionmentioning
confidence: 99%